Magnetic Nanosystem for Cancer Therapy Using Oncocalyxone a, an Antitomour Secondary Metabolite Isolated from a Brazilian Plant - Casagrande-Denardin, J (2013)
This paper describes the investigation and development of a novel magnetic drug delivery nanosystem (labeled as MO-20) for cancer therapy. The drug employed was oncocalyxone A (onco A), which was isolated from Auxemma oncocalyx, an endemic Brazilian plant. It has a series of pharmacological properties: antioxidant, cytotoxic, analgesic, anti-inflammatory, antitumor and antiplatelet. Onco A was associated with magnetite nanoparticles in order to obtain magnetic properties. The components of MO-20 were characterized by XRD, FTIR, TGA, TEM and Magnetization curves. The MO-20 presented a size of about 30 nm and globular morphology. In addition, drug releasing experiments were performed, where it was observed the presence of the anomalous transport. The results found in this work showed the potential of onco A for future applications of the MO-20 as a new magnetic drug release nanosystem for cancer treatment. © 2013 by the authors; licensee MDPI, Basel, Switzerland.